An efficient combination of transcritical CO2 refrigeration and multi-effect desalination: Energy and economic analysis. (1st November 2016) - Farsi, Aida; Mohammadi, S.M.Hojjat; Ameri, Mehran
Highlights: A novel combination of CO2 refrigeration and MED system is analyzed from energy and economic viewpoints. A new heating medium source in MED (supercritical CO2 ) is introduced. Heat transfer coefficients in components of the system are calculated. In MED, supercritical CO2 presents better heat transfer characteristics compared to steam. In similar operating conditions, the combined cycle is more economical than single generation systems. Abstract: This paper presents a novel combination of transcritical carbon dioxide refrigeration with Boosted-MED (Multi-Effect-Desalination) system to provide cooling and fresh water simultaneously. In the combined system a part of gas cooler in refrigeration system is replaced by the first effect and Booster module of Boosted-MED; so that a significant amount of waste heat would be recovered. Thermodynamic and economic analyses are carried out in order to investigate the proposed system's performance. Since institution of CO2 as a heating medium in MED systems is a novel topic; so, the heat transfer process between CO2 and seawater is studied. Results show that the supercritical CO2 presents an effective heat exchange process. Therefore, the specific heat transfer area would be reduced 135% and 25% compared to conventional MEDs and sensible heat source MEDs, respectively. The proposed combined system can save 57% of energy and 37.8% and 29.1% of total annual cost in Iran and Toronto respectively, compared to a stand-alone CO2 refrigeration system and an MED-Boosted.